VAR2/AtFtsH2 and EVR2/BCM1/CBD1 synergistically regulate the accumulation of PSII reaction centre D1 protein during de‐etiolation in Arabidopsis. (2nd June 2022) - Wang, Xiaomin; Li, Qinglong; Zhang, Yalin; Pan, Mi; Wang, Ruijuan; Sun, Yifan; An, Lijun; Liu, Xiayan; Yu, Fei; Qi, Yafei
Abstract: Thylakoid FtsH complex participates in PSII repair cycle during high light‐induced photoinhibition. The Arabidopsis yellow variegated2 ( var2 ) mutants are defective in the VAR2/AtFtsH2 subunit of thylakoid FtsH complex. Taking advantage of the var2 leaf variegation phenotype, dissections of genetic enhancer loci have yielded novel paradigms in understanding functions of thylakoid FtsH complex. Here, we report the isolation of a new var2 enhancer, enhancer of variegation2‐1 ( evr2‐1 ). We confirmed that EVR2 encodes a chloroplast protein that was known as BALANCE OF CHLOROPHYLL METABOLISM 1 (BCM1), or CHLOROPHYLL BIOSYNTHETIC DEFECT 1 (CBD1). We showed that EVR2/BCM1/CBD1 was involved in the oligomerization of photosystem I complexes. Genetic assays indicated that general defects in chlorophyll biosynthesis and the accumulation of photosynthetic complexes do not necessarily enhance var2 leaf variegation. In addition, we found that VAR2/AtFtsH2 is required for the accumulation of photosynthetic proteins during de‐etiolation. Moreover, we identified PSII core proteins D1 and PsbC as potential EVR2‐associated proteins using Co‐IP/MS. Furthermore, the accumulation of D1 protein was greatly compromised in the var2‐5 evr2‐1 double mutant during de‐etiolation. Together, our findings reveal a functional link between VAR2/AtFtsH2 and EVR2/BCM1/CBD1 in regulating chloroplast development and the accumulation of PSII reaction centre D1 protein during de‐etiolation. BRIEF SUMMARY: Functional characterizations of genetic enhancer loci, designated as ENHANCERs OF VARIEGATION ( EVRs ), of the Arabidopsis yellow variegated2 mutant have yielded novel paradigms in understanding the functions of VAR2/AtFtsH2 in chloroplast development. Here, we report that the EVR2 locus encodes a chloroplast protein EVR2/BCM1/CBD1 that was previously shown to be involved in chlorophyll biosynthesis. We provide evidence that EVR2/BCM1/CBD1 functions synergistically with VAR2/AtFtsH2 to regulate chloroplast development and the accumulation of photosystem II reaction centre D1 protein during de‐etiolation in Arabidopsis.